2013
DOI: 10.1002/jcph.179
|View full text |Cite
|
Sign up to set email alerts
|

Obesity impairs vasodilatation and blood flow increase mediated by endothelial nitric oxide: An overview

Abstract: Obesity dramatically increases the risk of development of cardiovascular and metabolic diseases. Endothelial dysfunction induced by obesity is an important risk factor that impairs blood flow controls in various organs. Impaired endothelial function occurs early in life in obese children. Obesity-induced endothelial dysfunction is associated with decreased nitric oxide (NO) production due to impaired endothelial NO synthase activity and expression and increased production of superoxide anion and the endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 115 publications
(200 reference statements)
2
41
0
Order By: Relevance
“…The regulation of endothelial NOS (eNOS) activity is regulated through glucose-mediated mitochondrial production of reactive oxygen species [22]. The subjects with hyper-duction, which is caused by impaired eNOS activity and expression, and increased production of superoxide anion and ADMA as well as vasoconstrictor factors, such as endothelin-1, and sympathetic nerve activation [33]. Uslu and colleagues reported that ADMA levels were correlated with hypoadiponectinemia and hyperleptinemia [34].…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of endothelial NOS (eNOS) activity is regulated through glucose-mediated mitochondrial production of reactive oxygen species [22]. The subjects with hyper-duction, which is caused by impaired eNOS activity and expression, and increased production of superoxide anion and ADMA as well as vasoconstrictor factors, such as endothelin-1, and sympathetic nerve activation [33]. Uslu and colleagues reported that ADMA levels were correlated with hypoadiponectinemia and hyperleptinemia [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity is known to be associated with increased plasma levels of ADMA, we did not observe significant differences between our normal weight and mildly obese patients. ADMA impairs endothelial NOS function and contributes to the cardiovascular complications often seen with obesity [20]. Moreover, recent findings suggest that eNOS impairment may also contribute to obesity by attenuating or preventing increases in metabolic activity in the adipose tissue [56].…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients have increased plasma levels of asymmetric dimethylarginine (ADMA) [20], a natural inhibitor of the endothelial nitric oxide synthase (NOS) function and nitric oxide production [20,21]. Endothelial NOS dysfunction decreases NO-dependent vasodilation and contributes to hypertension and other cardiovascular complications often seen with obesity [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering involving vascular dysfunction, mediated by endothelial nitric oxide and signaling during obesity and vascular regulation in renal dysfunction, the risk of development of cardiovascular and metabolic diseases dramatically increases. Endothelial dysfunction induced by obesity and concept of Flammer syndrome might have considered as an important risk factor including for stratification patients with MetS and kidney disease [77,78].…”
Section: Predictive Medical Approachmentioning
confidence: 99%